2015
DOI: 10.1038/bmt.2015.19
|View full text |Cite
|
Sign up to set email alerts
|

Risk model incorporating donor IL6 and IFNG genotype and gastrointestinal GVHD can discriminate patients at high risk of steroid refractory acute GVHD

Abstract: Steroid refractory acute GVHD (SR aGVHD) is associated with high morbidity and mortality. This study attempted to generate a risk model for SR aGVHD using 259 single nucleotide polymorphisms (SNPs) in 53 genes of recipients and donors. A total of 268 patients with aGVHD who were treated with systemic steroids were included. Patients were randomly divided into training (n = 180) and validation sets (n = 88). Clinical risk factors were also evaluated. In the training set, 85 (47.2%) developed SR aGVHD. Gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…In the light of their prior preclinical studies, their emergent clinical experience, and their recent observations, Alam and colleagues have suggested that specific donor IFNγ and IL6 SNP/genotypes correlate strongly with the risk of steroid refractory GvHD. 16 Our findings corroborate the observation that IFNγ and IL6 are critical to the development and progression of acute GvHD. In addition, the need to selectively block both IFNγR and IL6R to prevent and treat GvHD further supports the rationale for combining an anti-human IFNγR antibody with tocilizumab.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the light of their prior preclinical studies, their emergent clinical experience, and their recent observations, Alam and colleagues have suggested that specific donor IFNγ and IL6 SNP/genotypes correlate strongly with the risk of steroid refractory GvHD. 16 Our findings corroborate the observation that IFNγ and IL6 are critical to the development and progression of acute GvHD. In addition, the need to selectively block both IFNγR and IL6R to prevent and treat GvHD further supports the rationale for combining an anti-human IFNγR antibody with tocilizumab.…”
Section: Discussionsupporting
confidence: 89%
“…Previous reports have shown that ruxolitinib potently inhibits IL6R signaling, 9 that the anti-IL6R–blocking antibody tocilizumab reduces acute GvHD in allo-HSCT patients, 15 and that donor IFNG and IL6 single nucleotide polymorphisms correlate with gastrointestinal GvHD severity. 16 Together, these observations suggest that IFNγR and IL6R signaling critically mediate GvHD. To test this hypothesis, we performed allo-HSCT using Ifngr −/− T cells and anti-mouse IL6Rα antibody as described in Supplementary Figure 2 .…”
Section: Resultsmentioning
confidence: 90%
“…To the best of our knowledge, the effects of different SNPs in the IL‐6R gene have been examined in only one previous heterogeneous cohort of allotransplant recipients . In these two studies the effects on various end‐points of 256 different SNPs in various cytokine and cytokine receptor genes were examined, eight of these SNPs being in the IL‐6R gene .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the effects of different SNPs in the IL-6R gene have been examined in only one previous heterogeneous cohort of allotransplant recipients [30,31]. In these two studies the effects on various endpoints of 256 different SNPs in various cytokine and cytokine receptor genes were examined, eight of these SNPs being in the IL-6R gene [30,31]. However, this study did not examine the effects of SNPs known to functional effects on the IL-6 system, and they observed an association only between rs4845617 and ocular chronic GVHD [31].…”
Section: Discussionmentioning
confidence: 99%
“…The study carried out by Li et al suggested that GG genotype of IFN‐γ rs2069727 polymorphism had apparently different distributions between case and control groups, and might confer increased risk of hepatocellular carcinoma 25 . Alam et al reported the significant interaction of IFNG rs2069727 with gastrointestinal GVHD 26 . In this study, we also examined the association between rs1861494 polymorphism and susceptibility to AS in the study population.…”
Section: Discussionmentioning
confidence: 80%